Effect of Cattle Breed on Meat Quality, Muscle Fiber Characteristics, Lipid Oxidation and Fatty Acids in China - Xiangxue Xie; Qingxiang Meng; Zhenliang Cui; Liping Ren (Asian-Australasian Journal of Animal Sciences, 2012)
The objective was to compare meat quality, muscle fiber characteristics, lipid oxidation and fatty acids of Limousin (LIM), Simmtental (SIM), Luxi (LX), Qinchuan (QC) and Jinnan (JN) offered the same diet in China. After finishing, eight bulls from each breed were randomly selected for slaughter at 18.5 months old. Longissimus dorsi (ld) muscle was taken from the carcass for meat quality evaluations. Breed had little effect on most of meat and fat color parameters except for Hue and b* in which QC had lower values. LIM showed higher pH (24 h) and better water holding capacity than other breeds. LIM showed the lowest dry matter content but the highest crude protein. LX and LIM had higher percentage and density of red muscle fiber than other breeds. Lipid oxidations were significantly lower in LIM than in QC, with the LX, SIM and JN having the intermediate values. Compared to other four breeds, QC provided the highest values of polyunsaturated fatty acids (PUFA), n-6 fatty acids and n-3 fatty acids. In conclusion, LIM scored better on most of meat quality characteristics; however, local breeds such as LX and QC also had better muscle fiber characteristics and better fatty acids composition.